Parent's Care toward Students' Curricular and Extracurricular Activities (A Site Study at State Junior High School 2 Magelang) - Wargana, Budi (2011)
This research is to describe (1) parents' care about children extracurricular education in Public Junior High School 2 Magelang; (2) parents' care about children extracurricular education in Public Junior High School 2 Magelang. This research is a qualitative research with ethnography design. This research is conducted in Public Junior High School 2 Magelang. The resource persons in this research are the headmaster, vice headmaster on curriculum field, teacher and parents. Data collection method used is interview, observation, and documentation. Analyzing data started from (1) data reduction, (2) data presentation, and (3) drawing conclusion. Data validity uses credibility, transferability, conformability and dependability. The results show: (1) the parents' care about extracurricular education can be realized in the forms of (a) parents involvement in decision-making in school, such as setting APBS and school programs, (b) the provision of financial assistance in accordance with the established provision, (c) give input, opinion, and advice in a formal meeting held by school; (d) establish good communication with school personnel, (e) give respect and cooperative attitude in resolving student issues, (f) supervise the student's activity at home; (g) active in meeting of parents and teachers as well as the home visit program; (2) Parents' care about children extracurricular education can be realized in the forms of (a) give opinion on extracurricular that will be held; (b) give incidental fund or programmed, (c) give direction in choosing extracurricular program for children (d) give motivation, and supervision of children in extracurricular education.